2009
DOI: 10.1111/j.1742-7843.2009.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Betulin Elicits Anti‐Cancer Effects in Tumour Primary Cultures and Cell Lines In Vitro

Abstract: Betulin is a pentacyclic triterpene found in many plant species, among others, in white birch bark. The aim of the study was in vitro characterization of the anticancer activity of betulin in a range of human tumour cell lines (neuroblastoma, rhabdomyosarcoma-medulloblastoma, glioma, thyroid, breast, lung and colon carcinoma, leukaemia and multiple myeloma), and in primary tumour cultures isolated from patients (ovarian carcinoma, cervical carcinoma and glioblastoma multiforme).In this study, we demonstrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 29 publications
9
74
0
Order By: Relevance
“…This is consistent with our previous findings in breast cancer cells [13]. In addition, RASSF1C over-expression also reduces the effects of the anti-cancer agent, betulinic acid, which is known to decrease lung cancer cell proliferation [22]. This further supports the growth promoting and apoptosis attenuating actions of RASSF1C.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with our previous findings in breast cancer cells [13]. In addition, RASSF1C over-expression also reduces the effects of the anti-cancer agent, betulinic acid, which is known to decrease lung cancer cell proliferation [22]. This further supports the growth promoting and apoptosis attenuating actions of RASSF1C.…”
Section: Discussionsupporting
confidence: 92%
“…It does this, at least in part, by down-regulating PIWILI, cyclin B1, cyclin D1, bcl2 and up-regulating bax gene expression in several types of cancer cells, including A549 [22], [26], [27]. We have previously demonstrated that RASSF1C over-expression up-regulates PIWIL1 gene expression and thus we wanted to determine if RASSF1C over-expression would reduce the anti-proliferative effects of BA on lung cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, betulin, which differs from BA by a single functional group, was also described for its property to induce an antiproliferative effect on other human cell lines, such as hepatoma (HepG2) cells and lung adenocarcinoma (A549) cells [17]. Anticancer effects were also reported for neuroblastoma (SK-N-AS) cells and colon carcinoma (HT-29) cells [18]. However, as reported so far in several significant papers, BA remains the triterpene of choice for anticancer activity on both human and murine melanoma models.…”
Section: Resultsmentioning
confidence: 99%